Master regulators of neurogenesis: the dynamic roles of Ephrin receptors across diverse cellular niches - Dilan Rasool; Arezu Jahani-Asl (Translational Psychiatry)
Abstract The ephrin receptors (EphRs) are the largest family of receptor tyrosine kinases (RTKs) that are abundantly expressed in the developing brain and play important roles at different stages of neurogenesis ranging from neural stem cell (NSC) fate specification to neural migration, morphogenesis, and circuit assembly. Defects in EphR signalling have been associated with several pathologies including neurodevelopmental disorders (NDDs), intellectual disability (ID), and neurodegenerative diseases (NDs). Here, we review our current understanding of the complex and dynamic role of EphRs in the brain and discuss how deregulation of these receptors contributes to disease, highlighting their potential as valuable druggable targets.